Legends of origin - Roming, Edi (Santa Fe, NM The New Mexican, 1978)
When the Indian stories and myths of the world are told, it is of the people's emergence into a world already formed, but soft and unripe. The People too, were already created, but they were in search of a way to leave the world of darkness and emerge int the world of light This is one of those stories. The legends of the origins of the Tewa are deep and mysterious, yet are part of the living lore of the Rio Grande Valley.
Article on page 6 and 7.
Master list item #: 56
File location is in the New Mexico file Cabinet
Keywords: Indian Myth and Legends; Tewa Indians; Creation Stories; Rio Grande Valley, New Mexico